2010
DOI: 10.1515/jpm.2010.061
|View full text |Cite
|
Sign up to set email alerts
|

Maternal complications of fetoscopic laser photocoagulation (FLP) for treatment of twin-twin transfusion syndrome (TTTS)

Abstract: High-quality data on maternal complications of FLP are rare. With systematic assessment, the rate of adverse events is significantly higher. Underreporting has to be assumed. Further studies are required to confirm these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…There was a severe complication rate (Clavien‐Dindo grade III or IV) of 4.5% in women undergoing open fetal surgery and 1.7% undergoing fetoscopic surgery. This is in keeping with a previous multi‐centre review of maternal complications following laser photocoagulation for TTTS, which found a 1.0% rate of severe complications and a 5.4% total rate of complications across all studies; however, when the authors only included studies, which systematically assessed maternal complications as a primary or secondary outcome, this rose to 1.8% for severe and 17.4% for all complications.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…There was a severe complication rate (Clavien‐Dindo grade III or IV) of 4.5% in women undergoing open fetal surgery and 1.7% undergoing fetoscopic surgery. This is in keeping with a previous multi‐centre review of maternal complications following laser photocoagulation for TTTS, which found a 1.0% rate of severe complications and a 5.4% total rate of complications across all studies; however, when the authors only included studies, which systematically assessed maternal complications as a primary or secondary outcome, this rose to 1.8% for severe and 17.4% for all complications.…”
Section: Discussionsupporting
confidence: 87%
“…One single‐centre study of maternal outcomes following both open fetal and fetoscopic surgery performed between 1989 and 2003 found a number of short‐term morbidities . A systematic review of maternal complications following fetoscopic laser coagulation for twin‐to‐twin transfusion syndrome (TTTS) in 1785 patients treated between 1990 and 2009 observed an overall adverse event rate of 5.4% with severe complications in 1.0%. The aim of this study was to estimate the incidence of immediate and long‐term maternal complications of fetoscopic or open fetal surgery through a systematic review of the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review on the subject [12] reported that in the 3 existing studies with systematic assessment (379 patients) compared to those with unstructured approach, the rate of maternal complications after FLS was significantly higher (17.4 vs. 2.2%; p < 0.0001). The analysis quoted an overall rate of maternal events at 17%, with severe complications in 1.8%.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent analysis of the literature, the overall rate of adverse major and minor maternal events was 17%, with major events such as placental abruption and pulmonary or surgical sequelae occurring in less than 2% [12]. …”
Section: Introductionmentioning
confidence: 99%